PENGELOLAAN PROGRAM SCHOOL FOOD CARE DENGAN MENERAPKAN MANAJEMEN BERBASIS SEKOLAH UNTUK MEWUJUDKAN MUTU (STUDI KASUS DI SMP NEGERI 61 SURABAYA) - Khalimatus Sya'diyah; Erny Roesminingsih; Aris Sofandi (STKIP Pesisir Selatan, 2026)
Objective: This article discusses the importance of implementing SBM in managing school programs by emphasizing the application of 3 SBM principles to achieve school quality. The aim of this research is to describe and analyze the implementation of the principles of participation, transparency, and accountability in managing the School Food Care Program at SMP Negeri 61 Surabaya. The researcher used a qualitative approach with a case study design involving 4 informants as primary data, while secondary data was taken from articles and books. Data collection was done using observation, interviews, and documentation techniques. The results of the study show that the School Food Care Program has applied the 3 SBM principles, thus contributing to improving the quality of the school, indicated by the creation of a comfortable and conducive learning environment, fostering environmental care character, and strengthening the school's image through the achievements of the National Adiwiyata School 2025. However, the evaluation process depends on the situation since there are no success indicators written down in any document. The new thing about this research is that there are still few studies that discuss the application of MBS in managing school programs that use land in a complex way, including cultivation, environmental management, and waste utilization.